Hapax Legomenon διχοστασία in 1 Macc 3:29 and in Ancient Greek Literature - Nawrot, Janusz (The Biblical Annals, 2025)
The First Book of Maccabees contains many hapax legomena, including διχοστασία mentioned in the title of this article, recorded in 3:29. The author attempts to answer what role this term plays in the divinely inspired text and why it was used there. Is it a mere lexical enrichment of the author’s writing, or does it have a deeper theological meaning? Does it contain something that privileges it over other related terms since it was used? An analysis of the role of the term in question in 3:29 will help address the questions above. When writing about discord or rebellion, does the hagiographer employ other Greek concepts that he could also use in 1 Macc 3:29? Finally, what does Greek extra-biblical literature contribute to the understanding of the noun διχοστασία potentially influencing its intentional use in the verse under examination.